2003
DOI: 10.1046/j.1526-4610.2003.03209.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate as an Adjunctive Treatment in Migraine Prophylaxis

Abstract: These results suggest that topiramate is efficacious and safe as an adjunctive treatment in patients with migraine whose prior response to prophylactic management has been less than satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Topiramate in the prophylaxis of migraine 3.1 Episodic migraine 3.1.1 Topiramate compared with placebo and in open-label trials The efficacy and safety of topiramate in the prophylaxis of episodic migraine with and without aura were initially evaluated in small studies and case series [33][34][35][36]. Later, three 26-week, large randomized controlled trials (RCTs) (two North American and one European), with similar design and inclusion criteria, were carried out [37][38][39].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Topiramate in the prophylaxis of migraine 3.1 Episodic migraine 3.1.1 Topiramate compared with placebo and in open-label trials The efficacy and safety of topiramate in the prophylaxis of episodic migraine with and without aura were initially evaluated in small studies and case series [33][34][35][36]. Later, three 26-week, large randomized controlled trials (RCTs) (two North American and one European), with similar design and inclusion criteria, were carried out [37][38][39].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…This study demonstrated that over half the treated subjects responded to the combination treatment. A second open-label study investigated add-on treatment with topiramate in patients who responded inadequately to current prophylactic treatment, principally with propranolol or flunarizine (Martinez et al 2003). Again, headache frequency decreased after initiation of combination treatment.…”
Section: Prophylaxis Of Migrainementioning
confidence: 99%
“…Many studies have confirmed a significant therapeutic effect at the low dose of 100-200 mg/day, with the added advantage of better tolerability and lower discontinuation rates. Lower doses of topiramate are effective in migraine prophylaxis [50][51][52][85][86][87][88][89] and cluster headaches [90,91], partial-onset seizures [41,42,[92][93][94] and idiopathic generalized epilepsy [90].…”
Section: Tolerabilitymentioning
confidence: 99%